Clothing imagery as an offensive implement of warfare and honour within Psalms 108-110 - Sutton, Lodewyk (Journal for Semitics, 2017)
Within the trilogy of Psalms 108-110 clothing imagery portrays an important part in establishing the development of honour within these three psalms. Within Book V of the Psalms this trilogy presents a theme of restoration after war (after the Babylonian exile). This is accomplished through a strong use of warfare images that are mainly demonstrated through the use of body and clothing (armour) imagery. This imagery indicates and conveys a strong message of restoration and of honour for the nation. Within war, clothing is considered as part of the armour and functions as part of a soldier’s protection. Within Psalms 108-110 the clothing imagery takes on a different function as it becomes an offensive implement of warfare rather than a defensive implement. In this restorative function the clothing imagery strengthens the development of honour within Psalms 108-110.
free